2010
DOI: 10.1007/s00264-009-0938-3
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the distal humerus in elderly patients treated with a ring fixator

Abstract: The aim of distal humerus fracture treatment is articular surface reduction and stable fixation for early mobilisation and rehabilitation. This is usually performed by open reduction and internal fixation with plates. In the elderly osteoporotic patient this treatment is difficult to achieve due to fixation failure in fragile bone. We present our experience with treatment by closed reduction and external fixation with a non-bridging ring fixator in distal humerus fractures in elderly patients. There were ten f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…He noted that failure of fixation typically occurs in the distal fragment [14] which is more likely in low fractures. Alternatively, some reported placing the plates as distal as possible or adding an intermediate third or fourth plate if reconstruction with two plates is inadequate despite good bone stock [5]. Greiner et al reported preliminary results of the LCP in supra-intercondylar fractures and noted that clinical and radiological results are promising with good outcome [6].…”
Section: Complicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…He noted that failure of fixation typically occurs in the distal fragment [14] which is more likely in low fractures. Alternatively, some reported placing the plates as distal as possible or adding an intermediate third or fourth plate if reconstruction with two plates is inadequate despite good bone stock [5]. Greiner et al reported preliminary results of the LCP in supra-intercondylar fractures and noted that clinical and radiological results are promising with good outcome [6].…”
Section: Complicationsmentioning
confidence: 99%
“…Only two patients had heterotopic ossifications Brooker types I and II [7] Discussion Fractures involving the distal humerus are difficult to manage because of the complex anatomy. Many techniques have been described in the fixation of distal humerus fractures, such as double TBW [8], Y-plating [9], orthogonal plating, parallel position of the plates [10] and the DHP system [5].…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Elderly patients with fractures of the distal humerus have been treated with a ring fixator with satisfactory results. 7 External fixation may be mandated by a grade 3 open fracture of the distal humerus (Fig. 4).…”
Section: Open Reductioneinternal Fixationmentioning
confidence: 99%